Biologically-inspired evolving fuzzy ensemble - Liu, Yang (2012)
Neural fuzzy system is a hybrid intelligent system that synergizes artificial neural network and fuzzy logic techniques by combining the human-like reasoning style of fuzzy systems with the ability of learning and connected neural network structure. Existing neural networks have difficulty in learning from a dynamic data stream in the following aspects: 1) the limitation on the use of past explicit information poses difficulties in extending existing learning techniques; 2) the limited prior knowledge poses difficulties in designing a learning paradigm that can work without much prior information; 3) the sensitivity of learning methodology on the choice of the training parameters; 4) the unchangeable membership function width and 5) robustness of learning procedure against noisy or spurious data.